Bluebelle study (phase A): a mixed-methods feasibility study to inform an RCT of surgical wound dressing strategies. Issue 9 (22nd September 2016) - ,
Abstract : Objectives: Dressing primary surgical wounds is common, but the implications for surgical site infection (SSI) remain unknown. The Bluebelle study aimed to determine the feasibility of a randomised controlled trial (RCT) comparing 'simple', 'complex' or 'no' dressings on abdominal wounds, as prespecified in a funder's research brief. Bluebelle includes exploratory work (phase A) to inform a pilot version of the proposed RCT (phase B). Phase A aimed to investigate current dressing practices and perspectives on the proposed RCT, with a view to refining the forthcoming pilot. Design: Mixed methods, including semi-structured interviews and document analysis. Setting: 6 UK hospitals. Participants: 51 patients and 92 clinical professionals from abdominal surgical specialities. Results: Professionals had variable interpretations of what constitutes a 'dressing', particularly with respect to 'glue'—a product listed under 'wound-closure products' in the British National Formulary, which some surgeons reportedly applied as a 'wound covering'. Areas of ambiguity arising from interviews informed development of pragmatic definitions, including specification of conditions under which glue constituted a 'dressing'. Professionals reported that 'simple' dressings were routinely used in practice, whereas 'complex' dressings were not. This raised questions about the relevance of comparison groups, prompting the design of a survey to determine the types/frequency of dressing use in abdominal surgery (reported elsewhere). This confirmed that complex dressings were rarely used, while 'glue as a dressing' was used relatively frequently. 'Complex dressings' were therefore substituted for 'glue as a dressing' (following an updated Cochrane review, which found insufficient evidence to determine the effectiveness of 'glue as a dressing'). Patients and professionals acknowledged uncertainty around dressing use and SSI prevention, but felt dressings may serve practical and/or psychological benefits. This steered development of additional outcome measures for the pilot. Conclusions: Pre-trial qualitative research can highlight areas of ambiguity and inform new lines of enquiry in relation to prespecified research briefs, enabling adjustments to RCT design that enhance relevance to practice.